THE EFFECTIVENESS OF CONFLICT RESOLUTION STRATEGIES WITHIN NURSING TEAMS - Tahani Nazal Naqaa Alshammari, Manal Fnaitel Alanazi, Salwa Fnaitel Alanazi, Amani Saidan Zuman Alshammari, Noufah Abdulnasser Abdullah Alrashidi, Mutairah Muslim Alshammery, ‏Naimah Nasser Fahad Alanazi, ‏,; Mamdoh Muslt Saud Alshammry, Sultanah Rakyan Alruwalli, Mishal Darwish Suleiman Al-Shammari, Huda Yahya Bin Ahmed Absi, ‏Badriah Muqbil Mukhlef Alshammari, Mamdoh Saad Mohsen Algassab, (Chelonian Research Foundation, 2022)
The examination of conflict and nursing has produced an intricate collection of written works. Communication researchers give priority to interaction dynamics and provide well-developed theories. Nurse researchers give priority to the dynamics of a clinical setting. This study provides an overview of the field of organizational conflict studies, highlighting the progress made in social science research. It aims to provide a theoretical basis for conducting conflict research in the field of nursing. In nursing literature, conflict is described as a characteristic of the professional environment, often associated with emotions, namely incivility. Communication literature presents conflict as inherent and purposeful, emphasizing on matters while disregarding emotions. An effective strategy would include considering conflict processes from a communication perspective and understanding the working situation from a nursing one. Collaboratively, communication and nursing scholars may develop a nursing conflict resolution technique that surpasses the individual contributions of each field of study. This review corroborates that conclusion. Initially, it provides a concise overview of the existing body of research on organizational conflict. Subsequently, an examination and evaluation of nursing conflict research is conducted, taking into account conflict communication theory. This analysis emphasizes research that is firmly rooted in the field of social science. This study focuses on the extent of conflict among individuals and the interaction processes involved in conflict management, with a specific emphasis on nurses. However, it also includes other healthcare workers, typically doctors. Keywords: conflict, nursing, communication, working environment.